2005
DOI: 10.1590/s1415-47572005000200008
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive deficiency in bulls from synthetic breeds according to the type of crossbreed and the morphology of the Y chromosome

Abstract: We used 550 Braford and 214 Brangus-Ibagé bulls to study the association between Y chromosome morphology and the evaluation of breeding-soundness, karyotyping and breeding records were used to assess Y chromosome morphology. In general, no direct association was detected between the individual type of Y chromosome and reproductive fitness as previously estimated through breeding soundness examination. The type of breeding strategy used to form the synthetic breeds was also analyzed. The Braford breed is about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Several authors reported that almost 80-90% of purebred animals have no reproductive problems (Kennedy et al, 2002;Bjelland et al, 2011). In contrast, a greater proportion of bulls with reduced potential fertility was found in hybrids in comparison with their parental pure breeds (Horn et al, 2005). A synthetic breed (i.e., composite or hybrid or stabilizer) is a new breed or line from crossing two or more existing breeds, especially to increase hybrid vigor (Chacko, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported that almost 80-90% of purebred animals have no reproductive problems (Kennedy et al, 2002;Bjelland et al, 2011). In contrast, a greater proportion of bulls with reduced potential fertility was found in hybrids in comparison with their parental pure breeds (Horn et al, 2005). A synthetic breed (i.e., composite or hybrid or stabilizer) is a new breed or line from crossing two or more existing breeds, especially to increase hybrid vigor (Chacko, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At chromosome level, the Y-chromosome in Bos taurus is submetacentric while that in Bos indicus is acrocentric. Therefore, it was proposed that the lower fertility in zebu crosses with European cattle could be due to small deletions or position changes between the synapse region of the X and Y chromosomes, or to alterations in genes participating in the regulation of reproduction ( Horn et al, 2005 ). With the advancements in science and analytical techniques, nowadays, there is an increased interest in identification of male fertility markers.…”
Section: Introductionmentioning
confidence: 99%